Riflessioni sul tema delle “crociate tardive” La guerra al Turco tra Medioevo ed Età Moderna: ideologia e/o realtà politico-diplomatica - Merlani, Giulio (Études sur la Région Méditerranéenne, 2021)
This article aims to provide a general overview of the phenomenon of the so-called “late crusades”, analysing the ideological and political-diplomatic factors of the “contra Infedeles” war pursued by the Holy See between Middle Age and Modern Age. In this sense, particular attention was spent to the study of the key events of Nicopolis, Varna and Lepanto and then to underline the consequent transformation of the crusade in the Danubian- Balkan region between the 16th and the 17th centuries. In this way, we try to detect the aspects of continuity and evolution of the “Christian Holy War”, between the 14th and 17th centuries, in a double perspective, factual and ideal.